An unusual cause of dysphagia after gastric variceal bleeding - Jindal, Ankur (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Jindal A. An unusual cause of dysphagia after gastric variceal bleeding. Turk J Gastroenterol 2017; 28: 417-8